Information in radiotherapy for men with localised prostate cancer: An integrative review. (8th May 2019) - Gordon, Lynne; Dickinson, Angela; Offredy, Maxine
Abstract: Introduction: Men with prostate cancer may receive radiotherapy as part of their management. They encounter a range of information related to radiotherapy, and a crucial role for therapeutic radiographers and other healthcare practitioners is ensuring patients receive appropriate information related to their treatment. This integrative review aims to identify, synthesise and analyse literature reporting experiences of men with localised prostate cancer related to information in radiotherapy. Methods: A systematic literature search encompassing database and hand searches was carried out between February and March 2017 with date limits of 2000–2017 applied. Initially, 4, 954 articles were identified. Systematic screening and detailed examination identified that 33 met the inclusion criteria. Data were synthesised and analysed thematically. Results: Few studies explicitly addressed the issue of information in radiotherapy for men with localised prostate cancer. Themes that emerged and were explored are information needs, information regarding adverse effects, information and time, information preferences, satisfaction with information related to radiotherapy and patient experience related to radiotherapy information. Conclusion: This review suggests that although several aspects related to information for men with localised prostate cancer have been documented, few were explored in detail with respect to radiotherapy indicating that further research in this area is warranted.